Pengaruh Strategi Pembelajaran terhadap Dimensi Komitmen Organisasi Pada Karyawan Bank - Juliansyah Noor (The Asia Pacific Journal Of Management Studies, 2014)
This paper aimed empirically to determine the effect of learning strategies on organizational commitment and affective dimensions, continuance, and normative. The research sample of 80 respondents selected from employees of commercial banks in Indonesia with purposive sampling. Data analysis used regression model. The results showed that the dimensions of organizational commitment, affective, continuance, and normative were predicted by learning strategies. In other words, learning strategies has been a role in increasing employee commitment in the organization, having regard to the dimensions affective, continuance, and normative. Thus, learning strategies strongly associated with organizational commitment.